Food is the Asian Way of Showing Love: a Semiotic Analysis - Rizkhi Dinda Pratiwi; Umi Marfathonah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
This study aims to figure out the signs behind the